2016
DOI: 10.1186/s40478-016-0340-5
|View full text |Cite
|
Sign up to set email alerts
|

From animal models to human disease: a genetic approach for personalized medicine in ALS

Abstract: Amyotrophic Lateral Sclerosis (ALS) is the most frequent motor neuron disease in adults. Classical ALS is characterized by the death of upper and lower motor neurons leading to progressive paralysis. Approximately 10 % of ALS patients have familial form of the disease. Numerous different gene mutations have been found in familial cases of ALS, such as mutations in superoxide dismutase 1 (SOD1), TAR DNA-binding protein 43 (TDP-43), fused in sarcoma (FUS), C9ORF72, ubiquilin-2 (UBQLN2), optineurin (OPTN) and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
106
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(108 citation statements)
references
References 275 publications
(211 reference statements)
2
106
0
Order By: Relevance
“…Generally, the gene therapy strategy for sALS focuses on introducing neuroprotective agents like neurotrophic factors. The strategy for fALS focuses on addressing specific gene mutations [2,3]. On both fronts, preliminary research has shown progress, but successes are tempered by subsequent failures to scale up to translation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, the gene therapy strategy for sALS focuses on introducing neuroprotective agents like neurotrophic factors. The strategy for fALS focuses on addressing specific gene mutations [2,3]. On both fronts, preliminary research has shown progress, but successes are tempered by subsequent failures to scale up to translation.…”
mentioning
confidence: 99%
“…C9orf72 and NEK1) [3,13]. However, one great difficulty is that the symptomology and histology of ALS are not necessarily recapitulated in these models, meaning refinements are necessary [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The SOD1 rodent model is the most common animal model of ALS. Different gene mutations have been used in the SOD1 mice model [96] . There are heterogeneous phenotypical manifestations in SOD1 models with different gene mutations.…”
Section: Heterogeneity Of Als Animal Modelmentioning
confidence: 99%
“…There are heterogeneous phenotypical manifestations in SOD1 models with different gene mutations. These vary in rate of progression, time of symptom onset and pathological findings [96] .…”
Section: Heterogeneity Of Als Animal Modelmentioning
confidence: 99%